2015
DOI: 10.1001/jamaoto.2015.1172
|View full text |Cite|
|
Sign up to set email alerts
|

Safety of Adult Ambulatory Direct Laryngoscopy

Abstract: Adult ambulatory direct laryngoscopy has a favorable safety profile. Serious airway complications occur in fewer than 3 patients per 1000 cases. The risk of death following outpatient laryngoscopy is extremely low. Outpatient laryngoscopy is not universally suited for all patients, and careful preoperative selection and counseling are imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
3
26
1
Order By: Relevance
“…In this large, multistate cross‐sectional analysis, there was a revisit rate of 5.2% after ambulatory otologic surgery within the first 30 days. This closely compares to the 5.0% revisit rate after sinonasal surgery, similarly compares to revisit rate of 7.2% after ambulatory thyroidectomy, and is lower than the revisit rates after tonsillectomy (11.6%) and ambulatory uvulopalatopharyngoplasty surgery (9.7%), as reported in prior studies . Overall, our data indicate that ambulatory otologic surgeries are relatively safe procedures with a favorable safety profile.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this large, multistate cross‐sectional analysis, there was a revisit rate of 5.2% after ambulatory otologic surgery within the first 30 days. This closely compares to the 5.0% revisit rate after sinonasal surgery, similarly compares to revisit rate of 7.2% after ambulatory thyroidectomy, and is lower than the revisit rates after tonsillectomy (11.6%) and ambulatory uvulopalatopharyngoplasty surgery (9.7%), as reported in prior studies . Overall, our data indicate that ambulatory otologic surgeries are relatively safe procedures with a favorable safety profile.…”
Section: Discussionsupporting
confidence: 84%
“…A shift toward outpatient or day‐surgery cases has occurred over the last few decades in many areas within otolaryngology, including otologic surgery . Previously, we have described favorable complication and revisit rates for several nonotologic procedures .…”
Section: Introductionmentioning
confidence: 99%
“…21 There have been several publications in the surgical literature exploring factors associated with increased readmission rates, and the consensus among this data is that surgical complications have the greatest association with 30-day readmissions, but socioeconomic factors and patient comorbidities also have a significant impact. 15,[22][23][24][25][26][27][28][29] Although we did not find an association between readmission and socioeconomic factors, the presence of an outpatient tracheostomy-related complication carried the greatest odds of readmission on multivariable analysis.…”
Section: -Day Hospital Readmissionsmentioning
confidence: 89%
“…Of these procedures, the majority (57.2%) were performed in hospital‐based ambulatory surgery centers . Otolaryngology has increased the amount of outpatient procedures performed annually over the past 20 years, and data supports outpatient management of a wide range of otolaryngologic issues including pediatric disease, airway pathology, and sleep disorders . Further review of the NHSR data revealed that sinonasal procedures accounted for 600,000 ambulatory surgical visits in 2006.…”
Section: Discussionmentioning
confidence: 99%